A High Sensitive Flexible Pressure Sensor Designed by Silver Nanowires Embedded in Polyimide (AgNW-PI) - Hongfang Li; Guifu Ding; Zhuoqing Yang (Micromachines, 2019)
Silver nanowires (AgNW) have excellent electrical conductivity, transparency, and flexing endurance, and are broadly used in flexible electrodes and flexible sensors. This study mixed the silver nanowires and polyimide (PI) polymer using an in situ synthesis method, effectively reducing the problem of silver nanowires falling off the substrate. The selective wet etching method was firstly used to process the surface of AgNW-PI films, greatly enhancing the surface conductivity of AgNW-PI films. A flexible pressure sensor with high sensitivity was designed with two face-to-face AgNW-PI ultrathin layers. The experimental results show that our sensor presented a high sensitivity of about 1.3294 kPa−1 under a pressure of about 600 Pa, and when pressure continued to increase, the sensitivity decreased rapidly and reached saturation. Our flexible pressure sensor has the properties of low cost, high sensitivity, excellent repeatability, durability, and can detect various types of mechanical forces which could be utilized for flexible electronics.